A study on the guidelines of halal frozen food and its compliance in Shah Alam, Selangor / Hazida Suzana Hamzah … [et al.] - Hamzah, Hazida Suzana; Awang Sabu, Dayang Farzilla; Arisol, Nur Afiqah; Hussin, Sharida Citra (2009)
The purpose of this research is to avail the societies to a better awareness on the concept Halal irrespective of race, religion or creed and how Halal applies to not just Muslims but to everyone who wishes to have a good and high quality of life in every aspect. As we are on the pathway for the development towards the mission on exploiting Malaysia as an International Halal Food Hub in year 2010, we do hope through conducting this research will facilitate those with the responsibility for administering the legislation concerning the issue in hand, to come to terms with the current efforts to enact the main law on Halal food, Insyallah. This is important to increase Malaysian halal food industry competitiveness in the global market and to position Malaysia as a Global Halal Food Hub. This mission seems to have received broad support from industry, consumer groups and all political parties. However this masks divisions of opinion on Halal topics, notably the vexed question of whether there exist any parent Act concerning on the Halal food by the Malaysian Parliament, despite the existing 'guidelines' provided by JAKIM. This controversial issue has been massively debated to materialize the government's mission to sets the country to be the main Halal food hub and global Halal certification centre. This research is divided into six chapters. Chapter one will generally introduce on basis of the research, chapter two will touch on the literature reviews on Halal concept, chapter three will elucidate the development of the Halal food industry in Malaysia, chapter four focuses on the guidelines and its compliance whilst chapter five will discuss on the relevant Malaysian legislations. Lastly, chapter six outlines on the conclusions as well as the recommendations from the research.